The Role of Nursing Professionals in the Management of Patients With High-Risk Neuroblastoma Receiving Dinutuximab Therapy. (May 2017) - Secola, Rita; Marachelian, Araz; Cohn, Susan L.; Toy, Bonnie; Neville, Kathleen; Granger, Meaghan; Brentlinger, Angela; Martin, Gina
Neuroblastoma, an embryonic cancer of the sympathetic nervous system, is the most common extracranial solid tumor in childhood. Dinutuximab (formerly called ch14.18), a monoclonal antibody targeting the disialoganglioside GD2, has been shown to significantly improve survival rates in patients with high-risk neuroblastoma. However, the safe and effective use of dinutuximab therapy in these high-risk patients requires medical expertise in patient selection, treatment administration, and the monitoring and management of adverse events. Findings of the randomized phase III study (ANBL0032) led to the approval of dinutuximab for the treatment of children with high-risk neuroblastoma. Multi-institutional nursing approaches to implementing standard protocols ensure the effective management of high-risk neuroblastoma patients receiving dinutuximab immunotherapy. Understanding and implementing recommendations for the management of the clinically important and most common adverse events are essential to ensuring patient continuation of therapy and improving patient outcomes.